Studies on Diastereofacial Selectivity of a Chiral tert-Butanesulfinimines for the Preparation of (S)-3-Methyl-1-(2-piperidin-1-yl-phenyl)butylamine for the Synthesis of Repaglinide - Nagarajan, Periyandi; Rajendiran, Chinnapillai; Naidu, A.; Dubey, P.K. (Asian Journal of Chemistry, 2013)
A new method for the asymmetric synthesis of a series of chiral amines including (S)-3-methyl-1-(2-piperidin-1-yl-phenyl)butylamine (2a) a key intermediate to prepare antidiabetic drug repaglinide by using Ellman’s reagent tert-butanesulfinamide. Diastereoselective addition of organometallic reagents to t-butanesulfinimines and followed by acidic and basic treatment. The obtained chiral amines were characterized by NMR, MS and other analytical data.